Analysis of Factors Affecting Customer Loyalty and Customer Satisfaction of Netflix Users in Batam City - Cerina Cerina; Fendy Cuandra (Inovbiz: Jurnal Inovasi Bisnis, 2022)
This study aims to determine the effect of Promotion, Ease of Use, Brand Image, Service Quality and Website Quality on Customer Loyalty mediated by Customer Satisfaction. The sample in this study amounted to 400 people whose people are domiciled in Batam City and who have or are currently using the Netflix application. The sampling technique used is using the purposive sampling method in which the data used in this study is sourced from primary data such as distributing online questionnaires using Google Form. The final result of the study said that customer satisfaction was not influenced by promotion, but customer satisfaction was significantly influenced by ease of use, brand image, service quality and website quality. Then customer loyalty is significantly influenced by promotion, service quality, website quality and customer satisfaction, but customer loyalty is not influenced by ease of use and brand image.